5x-3-x=14-3x+11

Simple and best practice solution for 5x-3-x=14-3x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3-x=14-3x+11 equation:


Simplifying
5x + -3 + -1x = 14 + -3x + 11

Reorder the terms:
-3 + 5x + -1x = 14 + -3x + 11

Combine like terms: 5x + -1x = 4x
-3 + 4x = 14 + -3x + 11

Reorder the terms:
-3 + 4x = 14 + 11 + -3x

Combine like terms: 14 + 11 = 25
-3 + 4x = 25 + -3x

Solving
-3 + 4x = 25 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-3 + 4x + 3x = 25 + -3x + 3x

Combine like terms: 4x + 3x = 7x
-3 + 7x = 25 + -3x + 3x

Combine like terms: -3x + 3x = 0
-3 + 7x = 25 + 0
-3 + 7x = 25

Add '3' to each side of the equation.
-3 + 3 + 7x = 25 + 3

Combine like terms: -3 + 3 = 0
0 + 7x = 25 + 3
7x = 25 + 3

Combine like terms: 25 + 3 = 28
7x = 28

Divide each side by '7'.
x = 4

Simplifying
x = 4

See similar equations:

| 2k+8-4k=28 | | -18x^2+6x+24=0 | | Z^6=1 | | 23+14s=65 | | 23s+14=65 | | 3y^2-2x^2+2xy-6=0 | | 14x+3x+7x= | | 3.2=1.35h | | 2(j-20)+3=10 | | 3*1+y=9 | | 3*4+y=9 | | y-9=-11-y | | 4p-24=27-13p | | m-56=101 | | 3y+7=2y+7 | | 2y-5x=-60 | | w^2-9w+2=0 | | 4xsquared+3x+2x= | | o=364-120 | | (8x-4)-(9n-1)=12 | | C^2=0 | | 6(X+2)=2x+10 | | 15=-3(h-1)+9 | | 364=120+o | | 45y+11=20-54 | | 3(y+2)=15-y | | 2x-3=24x-135 | | 4(5p+6)=124 | | 6-y=20-4y | | 2y+3=11+y | | 2x+4x-3=11x-1 | | 4m+4m+2m+1+2m+3= |

Equations solver categories